(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
The digital transformation of global economies presents unprecedented challenges and opportunities for the auditing profession. This paper examines the necessity and approach for modernizing audit methodology to effectively address the complexities of digital business environments. The study synthesizes current literature and best practices to propose a comprehensive framework for contemporary audit implementation. Through the analysis of emerging technologies including artificial intelligence, blockchain, and cloud computing, the paper demonstrates how these technologies can enhance audit efficiency, effectiveness, and relevance. The research identifies critical gaps in traditional audit methodologies and proposes innovative approaches for digital-native audit processes. Key findings emphasize the importance of continuous adaptation, integrated technology platforms, and enhanced professional competencies in modern auditing. This paper contributes to the theoretical understanding of audit evolution and provides practical recommendations for audit practitioners and policy makers in the digital economy context.